Effects of chronic melatonin administration on pregnancy rate in dairy cows submitted to a fixed-time AI protocol during summer and winter seasons - Morini, Giorgio; Tummaruk, Padet; Saleri, Roberta; Rensis, Fabio De (The Thai Journal of Veterinary Medicine, 2023)
The aim of this study was to assess the effect of chronic melatonin treatment before calving in summer (long-day photoperiod, LDP, 16 h of light and 8 h of darkness) or winter (short-day photoperiod, SDP, 8 h of light and 16 h of darkness) on pregnancy rate after calving in lactating dairy cows. Before calving 60 cows were treated with melatonin and another 60 cows were not treated with melatonin thus functioning as a control group. In each group, 30 cows were treated during summer and 30 during winter. At 60 days after calving, all animals were submitted to a cosynch-ovsynch plus progesterone protocol and had fixed time artificial insemination (FTAI). The pregnancy rate at day 30 after FTAI was no different between groups (50% and 48% in treatment and in control groups, respectively, P = 0.66). Pregnancy losses during the first trimester of gestation (day 90 after FTAI) were 10% in cows treated with melatonin and 6% in the control group (P = 0.35). Considering the season of treatment there were no differences in either pregnancy rate (P = 0.70) or embryonic losses (P = 0.30) between the treatment and control groups. The results of this study indicate that in dairy cows submitted to a cosynch-ovsynch plus progesterone protocol and FTAI, the treatment with melatonin before calving did not compromise either pregnancy rate or embryo losses in both summer and winter.